"Save the Nerve": Technical Nuances for Hearing Preservation and Restoration in Vestibular Schwannoma Surgery: 2-Dimensional Operative Video. Issue 4 (25th June 2021) - Almefty, Rami O; Ibn Essayed, Walid; Al-Mefty, Ossama
Abstract: Hearing loss is a significant disability that inflects dysfunction and affects the patient quality of life. Consequently, hearing preservation and the potential of hearing restoration are prized quests in the management of vestibular schwannoma. 1 Although small intracanalicular vestibular schwannomas are commonly observed, progressive hearing loss occurs despite the absence of tumor growth; hence, surgical resection can be performed with the sole aim of hearing preservation in well-informed and eager patients. Hearing preservation by surgical resection has proven to be durable. 1-4 In this group of patients, we concur with Yamakami et al 2 that vascularized meatal flap to reconstruct the canal helps prevent scarring of the cochlear nerve and provides cerebrospinal fluid (CSF) bathing to the cochlear nerve, yielding better long-term hearing preservation.  With larger tumors and more severe hearing loss at presentation, microsurgical resection should aim at preserving the cochlear nerve, a goal frequently achievable, which offers the potential for hearing restoration with cochlear implants. 3 The results of cochlear implants in restoration of severe hearing loss have been to say the least most impressive. 5 We demonstrate these 2 frequently encountered clinical situations with 2 surgical videos showing specific surgical tenets, including intra-arachnoidal dissection, medial to lateral manipulation of the tumor, preservation of the labyrinthine artery, as well as reconstruction of the internal auditory canal. 2, 3, 6, 7 The patients consented to the surgery and to the publication of their picture in a surgical video.  Illustration in video © 1997 O. Al-Mefty. Used with permission. All rights reserved.